The Effect of Job Specifications and Training on the Performance of Employees at the Education Office of Palembang City - Napa Urbach; Naruliza, Esty; Mario, Asma; Yani, Ria Astri (Universitas Dehasen Bengkulu, 2025)
This study aims to determine the influence of job and training specifications on the Palembang City Education Office both simultaneously and partially. This study uses quantitative data. The sample method was used for 97 respondents with an error level of 10% or 0.1. The object of the research is all employees. The data used is primary data by distributing questionnaires directly to employees of the Palembang City Education Office. The test was carried out with SPSS version 26 through validity and reliability tests, classical assumption tests and hypothesis tests. The results showed that the value of the determination coefficient (R2) was 0.557 which means that the independent variable (X) affected 55.7% of the variable while the remaining 44.3% was influenced by other variables. Therefore, it can be concluded that silently and partially the specification of work and training has a significant effect on.